Attitudes of Psychiatric Nurses about the Request for Euthanasia on the Basis of Unbearable Mental Suffering(UMS). - Marc De Hert; Liesbet Van Bos; Kim Sweers; Martien Wampers; Jan De Lepeleire; Christophe U Correll (PLoS ONE)
Introduction When psychiatric patients express a wish for euthanasia, this should first and foremost be interpreted as a cry for help. Due to their close day-to-day relationship, psychiatric nurses may play an important and central role in responding to such requests. However, little is known about nurses' attitudes towards euthanasia motivated by unbearable mental suffering. Objectives The aim of this study was to provide insight into the attitudes and actions taken by psychiatric nurses when confronted with a patient's euthanasia request based on unbearable mental suffering (UMS). Method A questionnaire was sent to 11 psychiatric hospitals in the Flemish part of Belgium. Results The overall response rate was 70% (N = 627). Psychiatric nurses were frequently confronted with a request for euthanasia, either directly (N = 329, 53%) or through a colleague (N = 427, 69%). A majority (N = 536, 84%) did not object to euthanasia in a psychiatrically ill population with UMS. Confounding factors were the psychiatric diagnosis and the type of ward where the nurses were working. Most participants acknowledged a lack of knowledge and skills to adequately address the euthanasia request (N = 434, 71%). Nearly unanimously (N = 618, 99%), study participants indicated that dealing with euthanasia requests and other end-of-life issues should be part of the formal training of nurses. Conclusion The results highlight the need for ethically sound and comprehensive provision of care. Psychiatric nurses play an important role in dealing with the complex issue of requests for euthanasia. There is also a need for education, training and clear guidelines on the level of health care organizations.